1996
DOI: 10.3109/08916939608995333
|View full text |Cite
|
Sign up to set email alerts
|

Both TH1 and TH2 Cytokine mRNAs are Expressed in the NOD Mouse Pancreasin vivo

Abstract: In NOD mice, autoimmune recognition and destruction of pancreatic islet beta-cells appear to be independently regulated: all mice develop cellular infiltration of the islets (insulitis), but not all develop diabetes. The destructive potential of the insulitis lesion may depend on the balance between the two CD4+ T-cell subsets. TH1 and TH2, that mediate cellular-cytotoxic and humoral responses, respectively. With a semi-quantitative reverse transcriptase-PCR assay, we examined whether the disease process was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…High levels of these Th1-like cytokines after CY have also been demonstrated in control NOD mice in two independent studies [7,8,31]. Data on Th2 cytokines after CY are less concordant: Rothe et al found that IL-4 mRNA levels remained relatively constant after CY [7], while Faulkner-Jones et al described a rise in IL-4 mRNA levels [31]. In the present study we saw a diminished increase in Th1-like mRNA levels in 1,25(OH) 2 D 3 -treated NOD mice compared with controls after CY, but no significant differences in Th2-like cytokines after CY.…”
Section: Discussionmentioning
confidence: 83%
“…High levels of these Th1-like cytokines after CY have also been demonstrated in control NOD mice in two independent studies [7,8,31]. Data on Th2 cytokines after CY are less concordant: Rothe et al found that IL-4 mRNA levels remained relatively constant after CY [7], while Faulkner-Jones et al described a rise in IL-4 mRNA levels [31]. In the present study we saw a diminished increase in Th1-like mRNA levels in 1,25(OH) 2 D 3 -treated NOD mice compared with controls after CY, but no significant differences in Th2-like cytokines after CY.…”
Section: Discussionmentioning
confidence: 83%
“…An inherent dysregulation in Th1/Th2 cytokine production (Atkinson and Maclaren 1994;Beyhum et al 1997), as exemplified by altered production of and response to macrophage-and T-cell-derived cytokines, is associated with mouse models of type 1 diabetes (Faulkner-Jones et al 1996;Yoon et al 1998). Th1 cytokines, including IFN-γ and IL-2, induce islet β-cell destruction directly by activating CD8 + T cells, enhancing infiltration of these cells into the islets and releasing the synthesized cytotoxic mediators (Held et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Immunological abnormalities observed in type 1 diabetes are characterized by the presence of autoreactive antibodies against β-cell constituents and other autoantigens (Hagopian et al 1993), circulating autoreactive T cells (Shimada et al 1996), highly expressed adhesion molecules on T cells (Itoh et al 1993;Martin et al 1996), reduced serum levels of cytokine inhibitors (MandrupPoulsen et al 1994), and sustained expression of cytokines and their high-affinity receptors (Hussain et al 1996;Kolb et al 1996;Stewart et al 1993). Among them, T-cell-and macrophage-derived cytokines, especially Th1 cytokines such as IFN-γ and IL-2, are considered to play important roles in the destruction of β cells (Faulkner-Jones et al 1996;Karlsson et al 2000;Karlsson and Ludvigsson 1998;Rapoport et al 1998;Yoon et al 1998). On the other hand, a Th2 cytokine, IL-10, was also reported to accelerate autoimmune destruction of β islet cells (Pakala et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in most NOD mouse colonies (8) a clear sexual dimorphism is present showing high incidence of diabetes among females (60-90%) and low incidence among males (10-20%). Both CD4+ and CD8+ T cell subsets are required for development of diabetes in NOD mice (9)(10)(11)(12). However, the precise mechanisms by which T cells destroy ß cells are unclear.…”
Section: Introductionmentioning
confidence: 99%